Investigation of peste des petits ruminants outbreaks in goat farms of Chuadanga District of Bangladesh in 2014 - Islam, SK Shaheenur; Rao, Sangeeta; Akhter, AHM Taslima; Hossain, Md Mehedi; Islam, Mohammad Rafiqul; Islam, SM Sariful; Singha, Arun Kumar (Asian Journal of Medical and Biological Research, 2016)
A case-control study was conducted in Chuadanga district of Bangladesh to investigate risk factors for Peste des petits ruminants (PPR) that occurred during November-December 2014 in goat farms. A total of 37 farms were reported to be PPR cases based on active and passive surveillance from 4 villages of Chuadanga Sadar and Damurhuda sub-districts. Fifty-five control-farms were selected from the same 4 villages. Farmers of both case and control farms were interviewed using a pre-tested semi-structured questionnaire for data collection on potential risk factors. Logistic regression analysis was used to evaluate the association between potential risk factors and disease outcome. Focus group discussions with farmers and livestock personnel in the selected villages were conducted using participatory epidemiological (PE) approach to identify issues with PPR in the villages. The results showed that 27% of the case-farms (n=10) were vaccinated, 60% (n=6) of which were vaccinated two times and 40% (n=4) single time in a year. About 50% (n=20) farms used perch/macha and the other 50% used mud type of housing. The morbidity and case-fatality rate in case-farms were 15.49%, 54.54%, respectively. Adoption of single time annual vaccination and using perch/ macha housing were significant protective factors (OR=0.03, 95% CI=0.008-0.1, p<0.001; OR=0.29, 95% CI= 0.11-0.74, p=0.004 respectively). Vaccination done twice in a year significantly lowered infection when compared to one time vaccination (OR=0.21, 95% CI=0.05-0.79, p=0.02). The results from PE showed that proper labeling of PPR vaccines, logistics for mass vaccination and spreading awareness, are necessary for successful PPR prevention. In conclusion, control of PPR in this district may be achieved by single time annual vaccination with a maximum coverage along with adoption of perch housing in all goat rearing farms in the district. Asian J. Med. Biol. Res. December 2015, 1(3): 434-441